Employee Social Responsibility: A Missing Component in the ISI 26000 Social Responsibility Standard. (7th March 2018) - Hemphill, Thomas A.; Laurence, Gregory A.
Abstract: In this article, the focus is on developing a governance concept built on integrating the ISO 26000 Social Responsibility (SR) standard with an "employee social responsibility" (ESR) concept developed by the authors. To this end. The authors propose to compliment the voluntary, organizationally adaptable, ISO 26000 SR standard for the organization/firm with a seamlessly integrated—and equally adaptable—ESR concept for the individual/employee of that organization/firm. An SR/ESR governance concept emerges, with an emphasis on implementing a SR‐based business enterprise code of conduct and ESR‐related functional‐level codes of conduct, the latter firmly ensconced in an organization's ethical climate. The conclusion section discusses the strengths and weaknesses of our proposed SR/ESR governance concept.